PENGARUH KINERJA DAN VOLUME PERDAGANGAN TERHADAP HARGA SAHAM PERUSAHAAN PADA INDUSTRI PERBANKAN - Saiful Anam (Jurusan Akuntansi,Fakultas Bisnis dan Ekonomika,Universitas Surabaya, 2021)
The aim of this study is to (1) determine the effect of Return On Asset towards the Stock Price of banking companies in Indonesia Stock Exchange (2) determine the effect of Return On Equity towards the Stock Price of banking companies in Indonesia Stock Exchange (3) determine the effect of Earning Per Share towards the Stock Price of banking companies in Indonesia Stock Exchange (4) determine the effect of Trading Volume towards the Stock Price of banking companies in Indonesia Stock Exchange (5) determine the effect of Return On Asset, Return On Equity, Earning Per Share and Trading Volume towards the Stock Price of banking companies in Indonesia Stock Exchange. The population in this study is banking companies listed in the IDX. The selection of samples applies the purposive sampling method. The number of samples is 10 banking companies listed on the IDX in the period of 2015-2018. The data analysis used to test the hypothesis is the Multiple regression analysis technique. Based on the research, results show that (1) Return On Asset gives positive effect towards the Stock Prices (2) Return On Equity Asset have an insignificant effect towards the Stock Prices (3) Earning Per Share Asset gives positive effect towards the Stock Prices (4) Trading Volume Asset have an insignificant effect towards the Stock Prices.